Extraction Study on the Colour Reaction for Cobalt (II) with the 2-hydroxy-5-nitrothiophenol - Di-, triphenylamine - Water - Chloroform System - zalov, Ali Z.; Maharramov, Abel M.; Suleymanova, Geyser S.; Ibrahimova, Shahla A. Ibrahimova; Mamedova, Shafa A.; Verdizadeh, Naila A. (IJRDO-Journal of Applied Science, 2018)
The conditions for the complexation of cobalt (II) with HNTPh and Am (DPhА and TPhA) are optimized, such as the formation of the complex in time (300 minutes), pH of the medium (pHop 3.6-5.2), the excess of the reagent, and the conditions for obeying the Bouguer-Lambert-Beer law(0.06-20 μg / 5 ml). The spectral characteristics of the complex (λ= 560-565 nm) and the HNTPh reagent (λ= 295 nm) were studied which showed high sensitivity and contrast (λ= 265-270 nm) and the true molar coefficient (ε= (3.4-3.6)× 104) of light absorption was determined. The mole ratio of cobalt: agent is determined by two methods; the equilibrium shift method and the Asmus straight line method, and in both cases the Co: HNTPh: Am = 1: 2: 2 composition. The interval of obedience to the Bouguer-Lambert-Beer law (0.06-20 μg / 5 ml) and the Sendel sensitivity of 0.0111 - 0.0175 μg / cm2 are shown. Based on the achieved results and revealed regularities, a photometric technique for determining cobalt (II) with HNTPh and Am. The selectivity of the developed methodology was studied. The developed technique is applied to the analysis of various objects, the results obtained are processed by the method of mathematical statistics